Penguatan Kapasitas Mahasiswa Akuntansi Universitas Bumigora dalam Penulisan Proposal Penelitian - Ajiani, Ika Putri Fitri (Jurnal Ilmiah Pengabdian dan Inovasi, 2023)
The purpose of this community service is to provide additional in-depth insights regarding writing research proposals, especially for accounting students at Bumigora University. The KKN was held for two days with participants from final semester accounting students at Bumigora University. The result of this community service is that students are able to write research proposals systematically. This community service is expected to be sufficient provision for students to continue writing their research proposals.